A Model Framework for Cultivating Competencies in Trainee Doctors During Housemanship - Nor Shela Saleh; Mohd Shafie Rosli (Universiti Sains Islam Malaysia, 2025)
Sains Insani, Volume 9 Issue 2 Page (393-404)